2004
DOI: 10.1159/000076892
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Antigens Are Recognized by Antibodies Present in Sera of Patients with Multiple Sclerosis

Abstract: Multiple sclerosis (MS) is frequently accompanied by visual symptoms including those related to retinal disorders. Since they may be a consequence of an autoimmune reaction, we examined whether sera of patients with diagnosed MS and changes in visual-evoked potentials contain antibodies against retinal antigens (retAgs). Immunoblot analysis revealed that MS sera recognized mainly a 46-kD antigen, a 41-kD antigen, retinal arrestin, to a smaller extent also 70-, 56-, 43-, and 36-kD proteins. Patients whose sera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 15 publications
3
14
0
Order By: Relevance
“…Autoantibodies against NNE have also been implicated as a cause of autoimmune retinopathy (8)(9)(10). We, and others have reported the presence of anti-NNE antibodies in association with retinopathy in MS patients (11,12). Furthermore, we have reported an increased prevalence of enolase autoantibodies in MS patients compared to healthy controls (13).…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Autoantibodies against NNE have also been implicated as a cause of autoimmune retinopathy (8)(9)(10). We, and others have reported the presence of anti-NNE antibodies in association with retinopathy in MS patients (11,12). Furthermore, we have reported an increased prevalence of enolase autoantibodies in MS patients compared to healthy controls (13).…”
Section: Introductionsupporting
confidence: 59%
“…It is well known that MS is associated with intermediate uveitis (26)(27)(28) and arrestin can be used to induce experimental autoimmune uveoretinitis (EAU) (29)(30)(31). Autoantibodies to both brain and retina arrestin have been reported in MS patients (11,32,33), although the T-cell proliferative response to this antigen has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of autoantibodies to a 46-kD antigen identified as ·-enolase was reported in studies on CAR and other autoimmunity-based diseases [4,[25][26][27]. In sera of some cancer patients, neuronal Á-enolase was detected [28] and it was also possible that anti-p46 antibodies were directed against this protein.…”
Section: Discussionmentioning
confidence: 82%
“…We recently reported a case of retinal degeneration without clinical inflammation in a patient with MS who was found to have strong antibody reactivity against α-enolase [35]. Following this, another study found that antibodies against a 46 kDa protein (confirmed to be α-enolase) were present in 17 out of 28 (61%) of MS patients, and that some of the patients with high antibody titres had reduced electroretinograms (ERGs) and/or visual impairment [36]. This study, however, did not contain a detailed analysis of all ERG parameters with ISCEV standards.…”
Section: Introductionmentioning
confidence: 95%